Persistent headache and low back pain after accidental dural puncture in the obstetric population: a prospective, observational, multicentre cohort study. (23rd April 2021) - Niraj, G.; Mushambi, M.; Gauthama, P.; Patil, A.; Kelkar, A.; Hart, E.; Nurmikko, T.; ,
Summary: Accidental dural puncture following epidural insertion can cause a post‐dural headache that is defined by the International Headache Society as self‐limiting. We aimed to confirm if accidental dural puncture could be associated with persistent headache and back pain when compared with matched control parturients. We performed a prospective multicentre cohort study evaluating the incidence of persistent headache following accidental dural puncture at nine UK obstetric units. Parturients who sustained an accidental dural puncture were matched with controls who had undergone an uneventful epidural insertion. Participants were followed‐up at six‐monthly intervals for 18 months. Primary outcome was the incidence of persistent headache at 18 months. Ninety parturients who had an accidental dural puncture were matched with 180 controls. The complete dataset for primary analysis was available for 256 (95%) participants. Incidence of persistent headache at 18 months was 58.4% (52/89) in the accidental puncture group and 17.4% (29/167) in the control group, odds ratio (95%CI) 18.4 (6.0–56.7), p < 0.001, after adjustment for past history of headache, Hospital Anxiety and Depression Scale (depression) and Hospital Anxiety and Depression Scale (anxiety) scores. Incidence of low back pain at 18 months was 48.3% (43/89) in the accidental puncture group and 17.4% (29/167) in the control group, odds ratio (95%CI) 4.14 (2.11–8.13), with adjustment. We have demonstrated that accidental dural puncture is associated with long‐term morbidity including persistent headache in parturients. This challenges the current definition of post‐dural puncture headache as a self‐limiting condition and raises possible clinical, financial and medicolegal consequences. 요약: 국제두통협회는 경막외 카테터를 삽입 후 발생하는 우발적 경막천자는 자기 한정적이라고 보고하였다. 저자들은 짝지어 진 대조군 만삭 산모들과 비교할 때 우발적인 경막천자가 지 속성 두통 및 요통과의 연관성 여부 확인을 목표로 하였다. 저자들은 9개의 영국 산부인과에서 우발적인 경막천자 후 지 속적인 두통 발생률을 평가하는 전향적 다기관 코호트 연구 를 수행하였다. 우발적 경막천자를 경험한 만삭 산모들은 특 별한 탈이 없이 경막외 삽입을 받은 대조군과 짝지어졌다. 참 여자들은 6개월 간격으로 18개월 동안 추적 관찰되었다. 주요 결과 지표는 18개월 시점에 지속성 두통의 발생이었다. 우발 적 경막천자를 경험한 90명의 만삭 산모는 180명의 대조군과 짝지었다. 일차 분석을 위한 전체 데이터는 256명(95%)이 참여 하였다. 18개월 시점에서 지속성 두통 발생은 우발적 천공군 에서 58.4% (52/89), 대조군에서 17.4% (29/167)였으며, 두통의 과거력, 병원 불안 및 우울 척도(Hospital Anxiet y and Depression Scale; 우울)와 병원 불안 및 우울 척도(Hospital Anxiety and Depression Scale; 불안) 점수를 통제하였을 때 교차비(95% CI)는 18.4 (6.0‐56.7), p ‹ 0.001이었다. 18개월 시점에서 요통의 발생은 우발적 천자군에서 48.3% (43/89), 대 조군에서 17.4% (29/167)였으며, 교차비(95% CI)는 조정 후 4.14 (2.11‐8.13)였다. 저자들은 우발적인 경막천자가 만삭 산모 에서 지속적 두통을 포함한 장기적 morbidity와 관련됨을 입 증하였다. 이는 경막천자 후 두통이 자기 한정적 상태라는 현 재 정의에 대해 이의를 제기하며, 이에 가능한 임상적, 경제 적, 법의학적 결과들을 제기한다.